Análise da degradação por CO2 em cimento classe G com nanoalumina para aplicações em poços de armazenamento geológico de carbono - Schemmer, Luana Bottoli (2020)
The interest in implementing new technologies in research to mitigate carbon emissions into the atmosphere is growing. Based on this, the CCS technique consists in capturing and storing CO2 in geological storage, being considered the most effective technique in mitigating carbon dioxide emissions. Although this technology is promising, there is concern that the leakage of the injected fluid will be as small as promising, there is a concern that leakage of the injected fluid should be a small as possible, which, among the various forms of CO2 leakage, can occur through micro-cracks and/or pores in the well’s cement paste. Given this scenario, this work aims to analyze the degradation behavior of reference class G cement paste with mass replacement contents of 0.5 wt% and 1.5 wt% of nano-alumina (n-Al2O3). Due to the complexity of the nanoparticle dispersion, two techniques of nano-alumina dispersion were employed in order to analyze and compare the behavior of n-Al2O3, and the ultrasonic tip (SP) and planetary mill (MP) were used. For the simulation of conditions representative of an oil well, a reactor was used to perform the autoclave of 6 MPa and temperature of 60°C, and for the degradation process the specimens were immersed in CO2 saturated water at a pressure of 15 MPa and a temperature of 90°C for 21 days. After the degradation process, the specimens were characterized by microtomography, X-ray diffraction, field emission scanning electron microscopy, gas pycnometry, Vickers microhardness and compressive strength tests. In the presence of nano-alumina, the advance of the carbonation front is not restricted, but when dispersed well, the precipitation of carbonates in the pores of the cement paste is lower. The dispersion by planetary mill reduced the grain size of the cement, resulting in a denser matrix and limiting the advance of the carbonation front when in the absence of nano-alumina. The dispersion of the tip sonicator produced pastes with compressive strength close to that of the standard reference paste for substitution levels of 0.5% and about 45.5% higher for the content of 1.5%. The amount of nano-alumina that provided the best performance was 0.5% and the dispersion method that allowed to reach the best homogeneity was that of the tip sonicator.